Pengaruh Pengunaan Media Sosial Konten Keagamaan terhadap Pemahaman Pelajaran Agama Islam pada Siswa Sekolah Menengah Kejuruan Negeri Gudo - Qurrotu Aina Al Arofat; HM. Zaimuddin W. As’ad; Moh. Makmun (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to determine the effect of using religious content on social media on the understanding of Islamic Religious Education among students at SMK Negeri Gudo. The method used is quantitative with a correlational approach. The sample in this study consisted of 24 eleventh-grade students selected using purposive sampling. Data collection techniques employed a Likert scale questionnaire. The analysis results indicate a significant relationship between the use of religious content on social media and the understanding of Islamic Religious Education, as evidenced by a correlation coefficient value of 0.578 with a significance of 0.003 (< 0.05), indicating a moderate and significant correlation. This study concludes that social media can positively contribute to students’ religious understanding when used appropriately. This study also suggests that teachers and schools can utilize social media as an effective learning tool by guiding students to access quality and reliable religious content. Furthermore, it is crucial to improve students' digital literacy so they can effectively select information and avoid misleading content. Thus, the use of social media is not merely for entertainment but also as a tool that supports a more optimal understanding and strengthening of Islamic religious values.